2020
DOI: 10.1136/openhrt-2019-001199
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transcatheter aortic valve implantation on mechanical dispersion

Abstract: ObjectivesThe physiological determinants of left ventricular (LV) mechanical dispersion (MD) are not fully explored. We aimed to investigate the impact of afterload reduction and changes in ventricular conduction on LV MD after transcatheter aortic valve implantation (TAVI).MethodsPatients with severe aortic stenosis (AS) were examined in a prospective, repeated measures observational cohort study before and after an uncomplicated transfemoral TAVI in a single tertiary centre. LV MD was assessed by speckle tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…There was also excellent inter‐observer and intra‐observer reproducibility across all three vendors which is in keeping with reported intra‐class correlation values in previous LVMD studies 5,17–19 …”
Section: Discussionsupporting
confidence: 88%
“…There was also excellent inter‐observer and intra‐observer reproducibility across all three vendors which is in keeping with reported intra‐class correlation values in previous LVMD studies 5,17–19 …”
Section: Discussionsupporting
confidence: 88%
“…Its net effects on cardiac mechanics can be variable in different patients. Nevertheless, Klaeboe et al [57] further reported echo strain image study which showed a significant reduction in LV mechanical dispersion in TAVI patients without NO-LBBB. However, those with NO-LBBB after TAVI had actually worsened mechanical dispersion and were associated with a higher risk of mortality during a 22-month follow-up (HR 1.24).…”
Section: Effects Of Pacemaker and Bundle Branch Block On LV Remodelling And Outcomementioning
confidence: 97%